Pengaruh Capital Intensity, Inventory Intensity, dan Transfer Pricing terhadap Agresivitas Pajak - Aljundi, Muhammad Akras; Purwatiningsih, Purwatiningsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Tax aggressiveness has become a critical issue in corporate financial management, particularly in developing countries like Indonesia where tax compliance plays a significant role in national revenue. In the Consumer Non-Cyclicals sector, various operational and financial strategies may influence a firm's level of tax aggressiveness. This study aims to examine the effect of Capital Intensity, Inventory Intensity, and Transfer Pricing on Tax Aggressiveness among companies in this sector listed on the Indonesia Stock Exchange (IDX) during the period 2018–2023. This research uses a quantitative approach with panel data regression analysis. A purposive sampling method was applied to select a sample of 17 companies, with data obtained from their published annual financial reports. The analysis was performed using EViews 10 software to test the relationships between the variables. The findings indicate that, simultaneously, Capital Intensity, Inventory Intensity, and Transfer Pricing significantly influence tax aggressiveness. However, when tested individually, only Capital Intensity shows a statistically significant effect on tax aggressiveness. Inventory Intensity and Transfer Pricing do not have significant individual impacts. These results suggest that higher capital investment relative to total assets may provide opportunities or incentives for companies to engage in more aggressive tax practices. Meanwhile, inventory levels and transfer pricing policies, in this context, may not play a dominant role. These insights are valuable for regulators and policymakers in evaluating tax compliance behavior in the sector.